Blow-Up Time for Nonlinear Heat Equations with Transcendental Nonlinearity - Hee Chul Pak (Journal of Applied Mathematics)
A blow-up time for nonlinear heat equations with transcendental nonlinearity is investigated. An upper bound of the first blow-up time is presented. It is pointed out that the upper bound of the first blow-up time depends on the support of the initial datum.